A Causal Relationship Model of Entrepreneurial Orientation Market Orientation and Competitive Advantage Influence of Business Performance of Construction in the Central Region of Thailand - Sangsiri, Monthiralai; Pariwatnanont, Chongrug (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
In this thesis, the researcher examines (1) examine the influence of entrepreneurial orientation, market orientation, and competitive advantage on the business performance of construction firms in the central region of Thailand; (2) confirm the structural relationships among entrepreneurial orientation, market orientation, competitive advantage, and business performance of construction firms in the central region of Thailand; and (3) develop a causal relationship model of entrepreneurial orientation, market orientation, and competitive advantage affecting the business performance of construction firms in the central region of Thailand. The study focuses on four key constructs: entrepreneurial orientation, market orientation, competitive advantage, and business performance. A quantitative research approach was employed. Data were collected from 300 construction companies through questionnaires administered to business owners or their representatives. Descriptive statistics and Structural Equation Modeling (SEM) using the AMOS program were applied for data analysis. The findings indicated that entrepreneurial orientation, market orientation, and competitive advantage were at the highest level, while business performance was at a high level, with the internal process perspective rated the highest. The results further showed that entrepreneurial orientation, market orientation, and competitive advantage had significant positive effects on business performance. All hypothesized relationships were supported at the 0.05 level of significance.